Antioxidant effects of sulforaphane in human HepG2 cells and immortalised hepatocytes. (June 2019) - Liu, Peng; Wang, Wei; Tang, Jonathan; Bowater, Richard P.; Bao, Yongping
Abstract: Sulforaphane (SFN) has shown anti-cancer effects in cellular and animal studies but its effectiveness has been limited in human studies. Here, the effects of SFN were measured in both human hepatocytes (HHL5) and hepatoma (HepG2) cells. Results showed that SFN inhibited cell viability and induced DNA strand breaks at high doses (≥20 μM). It also activated the nuclear factor (erythroid-derived 2)-like 2 (Nrf2), and increased intracellular glutathione (GSH) levels at 24 h. Pre-treatment with a low dose SFN (≤5 μM) protected against hydrogen peroxide (H2 O2 )-induced cell damage. High doses of SFN were more toxic towards HHL5 compared to HepG2 cells; the difference is likely due to the disparity in the responses of Nrf2-driven enzymes and -GSH levels between the two cell lines. In addition, HepG2 cells hijacked the cytoprotective effect of SFN over a wider dose range (1.25–20 μM) compared to HHL5. Manipulation of levels of GSH and Nrf2 in HepG2 cells confirmed that both molecules mediate the protective effects of SFN against H2 O2 . The non-specific nature of SFN in the regulation of cell death and survival could present undesirable risks, i.e. be more toxic to normal cells, and cause chemo-resistance in tumor cells. These issues should be addressed in the context for cancer prevention and treatment before large scale clinical trials are undertaken. Highlights: Sulforaphane exhibited biphasic effects on cell viability and DNA integrity in both cancer and normal cells. Nrf2/GSH system was involved in the protective effects of sulforaphane against oxidative stress at low dose. Cancer cells showed higher basal level of detoxification enzymes such as CAT, HO-1 and NQO1 compared to normal cells. Cancer cells hijacked the cytoprotective effect of sulforaphane over a wider dose range compared to normal cells. The adverse effect of anti-cancer drugs (phytochemicals) might be under-estimated using cancer cell lines.